2009
DOI: 10.1073/pnas.0907994106
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr virus LMP2A bypasses p53 inactivation in a MYC model of lymphomagenesis

Abstract: Although Epstein-Barr virus (EBV) is linked to Burkitt's lymphoma (BL), the role of the virus in lymphomagenesis is unclear. LMP2A, encoded by EBV, can be detected in BL biopsies and has prosurvival functions. We generated mice expressing MYC and LMP2A in B cells. LMP2A/ -MYC mice show greatly accelerated tumor onset. Similar to previous work, we found p53 mutations in -MYC tumors; however, we detected no mutations in the rapidly arising LMP2A/ -MYC tumors. We further demonstrate that the p53 pathway is functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
65
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(70 citation statements)
references
References 35 publications
(57 reference statements)
5
65
0
Order By: Relevance
“…LMP1 decreases expression of both ATM and p53 (35,44). Furthermore, both LMP1 and LMP2A inhibit p53-mediated apoptosis (7,30,75). LMP1 and LMP2A have both been reported to inhibit lytic viral reactivation in vitro (3,67,68,74), and we recently reported that LMP1-and LMP2A-expressing B cells do not express early lytic viral proteins in EBV-infected humanized mice, even when mice are infected with a "superlytic" EBV mutant that results in high-level Z/BMRF1 expression (59).…”
Section: Discussionmentioning
confidence: 97%
“…LMP1 decreases expression of both ATM and p53 (35,44). Furthermore, both LMP1 and LMP2A inhibit p53-mediated apoptosis (7,30,75). LMP1 and LMP2A have both been reported to inhibit lytic viral reactivation in vitro (3,67,68,74), and we recently reported that LMP1-and LMP2A-expressing B cells do not express early lytic viral proteins in EBV-infected humanized mice, even when mice are infected with a "superlytic" EBV mutant that results in high-level Z/BMRF1 expression (59).…”
Section: Discussionmentioning
confidence: 97%
“…[17][18][19] These mice develop a fatal lymphoma within several months. We developed a transgenic mouse model to study the role of LMP2A in BL 20,21 by crossing -MYC transgenic mice 18 with mice that express LMP2A in B cells. 22,23 LMP2A/-MYC mice also develop tumors, and tumor onset is accelerated compared with -MYC mice The online version of this article contains a data supplement.…”
Section: Introductionmentioning
confidence: 99%
“…20,21 Alteration of the major tumor suppressor p53 is common in tumors from MYC transgenic mice. 19 However, the p53 pathway was functionally intact in LMP2A/-MYC tumor cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, LMP2A probably maintains cell survival by modulating Bcl-xL levels and Bcl-2 expression patterns in the absence of B cell receptor signaling (Portis and Longnecker, 2004). Other studies have shown that LMP2A can bypass the intact p53 pathway in the c-MYC model of lymphomagenesis (Bieging et al, 2009;. Interestingly, the regulation was selective for Bcl-2, since the NF-κB inhibitor apparently affects the levels of Bcl-2 only in LMP2A/HEL-Tg B cells, not in the Bcl-2-positive HEL-Tg B cell .…”
Section: Bcl-2mentioning
confidence: 99%